Bilateral Pulmonary Artery Banding before Norwood Procedure: Survival of High-Risk Patients - Schulz, Antonia; Sinzobahamvya, Nicodème; Cho, Mi-Young; Böttcher, Wolfgang; Miera, Oliver; Redlin, Mathias; Ovroutski, Stanislav; Photiadis, Joachim (The Thoracic and Cardiovascular Surgeon, 2020)
Background This study reports midterm results of high-risk patients with hypoplastic left ventricle treated with initial bilateral pulmonary artery banding (PAB) before secondary Norwood procedure (NP).Methods Retrospective study of 17 patients admitted between July 2012 and February 2017 who underwent this treatment strategy because diagnosis or clinical status was associated with high risk for NP. Survival was compared with that of patients who underwent primary NP.Results Mean Aristotle comprehensive complexity score for NP would have been 19.7 ± 2.6. Risk factors included obstructed pulmonary venous return (n = 9), body weight < 2.5 kg (n = 7), total anomalous pulmonary venous connection (n = 3), and necrotizing enterocolitis (n = 1). Ten patients had a score ≥ 19.5. Early survival after PAB was 82.4% (14/17). NP was performed in 14 patients after improvement of clinical condition at a median age of 56 days and a weight ≥2,500 g. There was no 30-day mortality, but one interstage death. One patient died later after Glenn operation. One-year survival after primary PAB followed by NP was 70.6 ± 11.1%. During the same period, 35 patients with overall lower risk factors underwent primary NP; early postoperative survival and 1-year survival were 88.6 ± 5.4% and 68.6 ± 7.8%, respectively. There was no significant difference in survival between the two groups (p = 0.83) despite higher risk in the secondary Norwood group (p <0.0001).Conclusions PAB before NP in high-risk patients constituted salvage management. Primary PAB provided enough time for stabilization and control of most risk factors. It allowed midterm survival equivalent to the survival after primary NP in lower risk neonates.
Keywords: pulmonary artery banding; hypoplastic left heart syndrome; Norwood procedure; four-staged palliation